RELATIONSHIP BETWEEN DISCIPLINARY ATTITUDE WITH THE STUDENT LEARNING OUTCOMES OF VII KELAS IN STATE 14 OF SMP JAMBI - Riana, Puspa Cantika; Oktavia, Yellya (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The purpose of this study is; to find out the Relationship between Learning Outcomes of Discipline Character in Jambi State Junior High School 14. This type of research is research or relationship research. The research was carried out in classes VII D and VII E. The time of the study was carried out in the even semester of the academic year 2018/2019. The number of sample respondents in this study were 60 students. The technique of collecting data in this study uses a questionnaire technique to obtain student character data consisting of 25 items of questions then the test technique used to collect data, specific physics science learning achievement consisting of 30 items. This study uses quantitative research methods, which consist of quantitative data and analysis using correlation analysis techniques. The results of the analysis conducted by researchers indicate that disciplinary character education is significantly related to the learning outcomes of students of class VII D and VII E Jambi 14 Middle School. This can be proved by the Person Correlation = 0.976 with a significance level = 0.000. To determine the significance of the relationship between disciplinary character education and student learning outcomes can be done by looking at the significance level, where the test examines the opinion of the significance level smaller than 0.05 (95% confidence level) then a significant relationship between the independent variable and the dependent variable is needed. Based on the results of calculating a significant value smaller than 0.05 which is 0,000 <0.05. Therefore, it can be acknowledged that there is a relationship between disciplinary character education on the learning outcomes of students of class VII D and VII E in the Junior High School 14 of Jambi City.